A mobile wind turbine design for emergencies in rural areas - KUZUCUOĞLU, AHMET EMİN (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Electrical energy sources are one of the main needs after natural disasters such as earthquakes and tornadoes not only for emergency response teams but also for survivors' use. In such cases, the use of renewable energy sources is not very common. Generally, generators that use fossil fuels are commonly used. One of the main reasons for preference is that the generators of renewable energy sources are generally of static structure. Another reason is that renewable energy sources are not stable. However, this reason changes in rural areas. Because there are certain areas with high wind intensity in rural areas. If it is possible to reach the windy place, the wind turbines to be installed will help meet the electricity needs such as, the illumination of tent cities. Furthermore, it can be used by search and rescue, health, and safety teams. The main aim of the study is to design a renewable energy source that can be easily transported to different places for the mentioned reasons. In this study, a small 4-bladed vertical wind turbine that can be mounted on a 4 wheel-drive skid-steering ground vehicle is designed for use in the mentioned situations. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Vertical wind turbine; 4-WD ground Vehicle; Mobile wind turbine; Vertical blade; Energy for emergencies; PERFORMANCE